Comparing maxillary first molar crown shape using elliptical Fourier analysis in the Late Neolithic cave burials of Belgium - Bryan, Brandon Cory; Williams, Frank L’Engle (Anthropological Review, 2021)
The Belgian Meuse karstic basin holds more than 200 Late Neolithic collective burials. Four of the largest include Hastière Caverne M, Hastière Trou Garçon C, Sclaigneaux and Bois Madame. The remains from these caves are commingled and fragmentary. However, in situ maxillary molars are well preserved permitting an investigation of molar crown shape within and across sites. Crown outlines from the burials are compared using elliptical Fourier analysis to capture shape distinctions in the relatively numerous first maxillary molars (n = 27). Elliptical Fourier analysis is designed to compare deviations between each shape outline and an idealized ellipse, recorded as amplitudes of the harmonics which are reduced to principal components (PC) scores. We expect individuals from each site will be more similar to one another than to other internments in PC scores, and that the sites will be distributed along PC axes according to differences in chronology and geographic location. Principal components analysis reveals that individuals tend to cluster together based on cave burial as well as time period. Geographic distance only differentiates the final/late Neolithic cave burials. The earliest of the sites, Hastière Caverne M, is distinctive and includes multiple outliers. Hastière Trou Garçon C from earlier in the Late Neolithic does not cluster with Hastière Caverne M as expected. Instead, this cave burial groups with Sclaigneaux, the most geographically distant site but chronologically the closest to Hastière Trou Garçon C. Although the limited sample sizes for each site must be considered, it appears that early farmers of the Belgian Meuse basin exhibited intricate human population dynamics which may have included small, semi-isolated groups early in the Late Neolithic and larger communities with greater contact toward the onset of the northern European Bronze Age.